Laser Ablation – Cavity Ring Down Spectrometry: A new technique for water isotope measurements on ice cores - Eirini Malegiannaki; Vasileios Gkinis; Simon Alexander Munk Wael Fassel; Daniele Zannoni; Giuliano Dreossi; Barbara Stenni; Prof. Hans Christian Steen-Larsen; Pascal Bohleber; Carlo Barbante; Dorthe Dahl-Jensen (INQUARoma2023, 2023)
The Beyond Epica – Oldest Ice Core (1.5 Myr) which is being drilled in Antarctica will be a valuable paleoclimate archive and the water isotopic signal imprinted in the ice core layers will be one of the most important parameters to be measured. The extremely thin nature of the deep ice core layers requires measurements at very high resolution together with high precision and accuracy. A novel and promising measurement technique, which is being developed, couples Laser Ablation (LA) with Cavity Ring Down Spectrometry (CRDS) aiming to obtain high quality measurements. Laser Ablation (LA) is used as a micro-destructive sampling method, which is important for using the minimum amount of the valuable ice core samples, and allows not only high spatial resolution, but also fast and direct transition from solid to gas phase, when appropriate laser systems are employed. Craters, created on ice after the laser ablation process, are to be characterized along with varying laser parameters for the optimization of the controlling factors which lead to efficient LA sampling. Furthermore, designing an ablation chamber and a transfer line with the optimal shape and size is crucial for collecting the ablated material which should reach the high precision CRDS analyzer with minimum delivery disturbance.